Economic substantiation of outsourcing the information technologies and logistic services in the intellectual and innovative activities of an enterprise - Pererva, P. G.; Kuchynskyi, Volodymyr; Kobielieva, Tetiana; Kosenko, Andriy; Maslak, Olga (Технологический центр, 2021)
It has been proven that modern information and logistic technologies are the most important resource of the post-industrial society. It was proved that not every enterprise has a possibility to ensure its information and logistic activities using its own capabilities, so the possibilities of using outsourcing systems are becoming especially relevant. General features of outsourcing of information technologies and logistic services were determined. The most important of them include the mandatory existence of interaction between a supplier and a customer regarding the business processes of an enterprise. It was substantiated that several important types of outsourcing are used in the area of intellectual innovation activities of enterprises: complete and partial outsourcing, outsourcing of a joint type, outsourcing of the intermediate type, outsourcing of intellectual and innovative type. The method for synthesis of indicators of economic efficiency of outsourcing of information and logistic services of direct and indirect action for the economic evaluation of its effectiveness was proposed. This approach makes it possible to fully evaluate the benefits of outsourcing in comparison with the variant when they are implemented by an enterprise using its own capabilities. The basis of the proposed method is the ratio of indicators that reproduce the advantages obtained due to outsourcing. The implementation of this method makes it possible to ensure an important relationship between the process of development of information or logistic service and the required quality. Studies conducted at the enterprises of the Kharkiv industrial region showed that only three out of eight studied enterprises have economic grounds for using outsourcing. From the economic point of view, it is more expedient for other enterprises to carry out information (logistic) provision of their activities using their own resources.

Доведено, що найбільшважливим ресурсом постіндустріального суспільства є сучасні інформаційні та логістичні технології. Доведено, що далеко не кожне підприємство має змогу забезпечити свою інформаційну та логістичну діяльність власними силами, тому особливу актуальність набувають можливості використання систем аутсорсингу. Визначено загальні ознаки аутсорсингу інформаційних технологій та логістичних послуг. Найбільш важливою з них є обов'язкова наявність взаємодії постачальника і замовника щодо бізнес-процесів підприємства. Обґрунтовано, що в сфері інтелектуально-інноваційної діяльності підприємств використовуються декілька важливих видів аутсорсингу: повний і частковий аутсорсинг, аутсорсинг сумісного виду, аутсорсинг проміжного виду, аутсорсинг інтелектуально-інноваційного виду. Запропоновано метод синтезу показників економічної ефективності аутсорсингу інформаційних та логістичних послуг прямої і непрямої дії для економічноїоцінки ефективності його використання. Такий підхід дозволяє в повній мірі оцінити переваги використання аутсорсингу в порівнянні з варіантом їх виконання власними силами підприємства. В основу пропонованого методу покладено співвідношення показників, яківідтворюють переваги, щобули отримані за рахунок використання аутсорсингу. Впровадження даного методу дозволяє забезпечити важливий зв'язок між процесом розробки інформаційної або логістичної послуги та необхідною якістю. Проведені дослідження на підприємствах Харківського промислового регіону показали, що тільки три з восьми обстежених підприємств мають економічні підстави для використання аутсорсингу. Іншим підприємства більш доцільно з економічної точки зору здійснювати інформаційне (логістичне) забезпечення своєї діяльності власними силами.
Економічне обґрунтування аутсорсингу інформаційних технологій та логістичних послуг в інтелектуально-інноваційній діяльності підприємства
Keywords: outsourcing; information technology; logistic services; innovation activity; economic effectiveness; indicators; аутсорсинг; інформаційні технології; логістичні послуги; інноваційна діяльність; економічна ефективність; показники